2016
DOI: 10.1007/s10995-016-2187-6
|View full text |Cite
|
Sign up to set email alerts
|

A Call to Revisit the Prenatal Period as a Focus for Action Within the Reproductive and Perinatal Care Continuum

Abstract: Objectives The broad maternal and child health community has witnessed increased attention to the entire continuum of reproductive and perinatal health concerns over the past few years. However, both recent discouraging trends in prenatal care access and utilization and a renewed understanding of prenatal care as a critical anchor of the reproductive/perinatal health continuum for women who do get pregnant demand a new effort to focus on the prenatal period as a gateway for maternal and infant health. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Studies in the provinces of Manitoba and Newfoundland have shown that participation in prenatal support programs may improve birth outcomes [ 24 , 25 , 65 ]. Handler and Johnson [ 66 ] refer to prenatal care as “a critical anchor of the reproductive/perinatal health continuum for women who do become pregnant, often providing a woman’s first encounter with the health care delivery system” (p. 2221) The factors associated with inadequate prenatal care in this study offer some direction for improving use of prenatal care through strategies such as reduction of teenage pregnancy, optimal birth spacing, cessation of smoking and drug abuse, provision of social support, and providing an income supplement during pregnancy such as the Manitoba Prenatal Benefit [ 25 ]. Other authors have recommended paying special attention to socially vulnerable women to reduce variations in use of prenatal care [ 39 , 67 ] or more systematic attention to the roles of social disadvantage [ 68 ], and using a multidisciplinary approach [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the provinces of Manitoba and Newfoundland have shown that participation in prenatal support programs may improve birth outcomes [ 24 , 25 , 65 ]. Handler and Johnson [ 66 ] refer to prenatal care as “a critical anchor of the reproductive/perinatal health continuum for women who do become pregnant, often providing a woman’s first encounter with the health care delivery system” (p. 2221) The factors associated with inadequate prenatal care in this study offer some direction for improving use of prenatal care through strategies such as reduction of teenage pregnancy, optimal birth spacing, cessation of smoking and drug abuse, provision of social support, and providing an income supplement during pregnancy such as the Manitoba Prenatal Benefit [ 25 ]. Other authors have recommended paying special attention to socially vulnerable women to reduce variations in use of prenatal care [ 39 , 67 ] or more systematic attention to the roles of social disadvantage [ 68 ], and using a multidisciplinary approach [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gross disparities in these and other reproductive health outcomes are grounds for “evidence-based outrage” [70]. National initiatives to tackle disparities and rising rates of maternal morbidity and mortality [7173] make a renewed focus on prenatal care access, structure, content and quality not only timely, but essential [74]. …”
Section: Discussionmentioning
confidence: 99%
“…5 Although AA women are nearly twice as likely to suffer from pregnancy complications and multiple comorbidities, they are less apt to use health care after delivery than white women. 1,2 Further, at 40 deaths per 100,000 live births, the maternal mortality rate for AA women is 2 to 3 times greater than that for all other racial or ethnic groups. 5,6 Poor PNC utilization may be a factor associated with poorer maternal health outcomes, including the aforementioned.…”
mentioning
confidence: 97%
“…renatal care (PNC) remains a critical anchor in the continuum of women's health care given that nearly 3 of every 4 women will give birth at least 1 time in their lifetime. 1 For many women, PNC represents their first encounter with the healthcare system since childhood. 1 As such, PNC presents the opportunity for healthcare providers to offer health education 1−3 and identify or monitor underlying chronic medical conditions and pregnancy complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation